PEMAHAMAN SISWA TERHADAP KESELAMATAN DAN KESEHATANKERJA DI WORKSHOP KAYU JURUSAN BANGUNAN SMK N 1 KEC. GUGUAK KAB. 50 KOTA - 633-645 , Satria Septinova (Universitas Negeri Padang, 2015)
Abstract This researching of background from lot of the student still not folowing the rules of safety and healthy on work, besides that rules of safety and healthy have installed on the wall use the slogans, but the student still have a conversation while working use the machine, and the student not use safety equipment while working to. This research is a descriptive research, that have a purpose for reveal how much level of comprehension student about safety and healthy of work at carpenter workshop of Department Building at SMK N. 1 Sub-district Guguak, Regency of 50 Kota. Therfore expressed a question of research is how high the level of comprehension of student about safety and healthy of work at carpenter workshop of Department Building at SMK N. 1 Sub-district, Regency of 50 Kota, at school years 2013/2014 amount 52 students. The prime data of this research is dispersion or quisionaire for student building engineer. The flow of analisys consist of, (1) tabulation of data, (2) analisys data, (3) count the average of percentage scale of interval. Based on the analisys of data, be obtained knowledge the student about safety and healthy of work at carpenter workshop of Department Building at SMK N. 1 Sub-district Guguak, Regency of 50 Kota is 71.23% and middle classified. Keyword: Comprehension. Safety and Healthy of Work.